Atrial mechanics in anthracycline chemotherapy: insights into a prospective study. (4th February 2022) - Vahabi, S; Kharati-Koopaei, E; Norouzi, M; Maddox, J; Humphreys, A; Hancock, H; Zaman, A; Austin, D
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): South Tees Research and Development Fund Background In cancer treatment, detection of anthracycline induced cardiotoxicity (AIC) has been dependent on serial cardiac imaging to identify a reduction in left ventricular ejection fraction (LVEF) and more recently LV global longitudinal strain (GLS). However, studies have failed to assess the adverse effects of these agents on other cardiac chambers such as the left (LA) and right atria (RA). Purpose The PROACT PLUS study is an observational, prospective, cohort study investigating the effects of anthracyclines on the left and right atrial mechanics using 2 dimensional speckle tracking echocardiography (STE). We hypothesize that anthracyclines can affect the heart as a whole rather than solely affecting the LV. Methods From October 2018 to March 2020, patients with a new diagnosis of lymphoma or breast cancer receiving anthracycline chemotherapy were recruited into this study. Echocardiography was performed pre-chemotherapy (V1) and 1 month post-chemotherapy (V2). LA and RA volumes, LA (4-chamber)- and RA GLS, reservoir strains (RS), conduit strains (CS), contractile strains (CoS), peak-systolic (PS) strain-rates, early-diastolic (ED) strain-rates, and late-diastolic (LD) strain-rates were measured offline using vendor-independent software. This study was ethically approved by the Health Research Association (REC reference 18/EM/0177). Results A total number of 62 patients were recruited into this study. Unfortunately, 7 patients passed away during their treatment and 5 failed to attend their follow-up appointment at V2. From V1 to V2, there was a significant deterioration in the LA CS (-18.1% vs. -14.5%, p = 0.02) and LA ED strain-rate (-1.24 1/s vs. -0.86 1/s, p = 0.001). There was no other statistical significant change in the LA volume or other strain parameters. Additionally, there was a statistically significant decline in RA GLS (34.9% vs. 30.8%, p = 0.029), RA RS (41.1% vs. 37.1%, p = 0.03), RA CS (-23.8 vs. -20.6, p = 0.05), and RA ED strain-rate (-1.17 vs. -0.99, p = 0.02) with no significant change in the RA volume and other measures of RA strain. Conclusion: These findings support our hypothesis that anthracyclines exert their cardiotoxic effects on all cardiac chambers including the atria. Whether these changes lead to subsequent permanent structural abnormalities in the atria hence increasing the future risk of atrial arrhythmias, or whether these changes predate subsequent cardiac dysfunction and poor prognosis, remains unknown. Long-term follow up and assessment of atrial mechanics is crucial in better understanding of AIC to help guide the future monitoring and management of patients undergoing cancer treatment.